Hypomethylation of MIR‐378 5'‐flanking region predicts poor survival in young patients with myelodysplastic syndrome. Issue 1 (13th December 2019) - Wu, De‐hong; Zhu, Xiao‐wen; Wen, Xiang‐mei; Zhang, Ying‐ying; Ma, Ji‐chun; Yao, Dong‐ming; Zhou, Jing‐dong; Guo, Hong; Wu, Peng‐fei; Zhang, Xing‐li; Qiu, Hong‐chun; Lin, Jiang; et al.
Abstract: Background: Previous studies have disclosed up‐regulation of MIR‐378 in acute myeloid leukemia (AML), and might consequently affect the outcome of the patients. Correspondingly, hypomethylation of MIR‐378 was also identified in AML, particularly for FAB‐M2 subtype with t(8;21) chromosomal translocation. Nevertheless, the methylation status of MIR‐378 has not been illustrated in myelodysplastic syndrome (MDS). Herein we designed to understand the methylation pattern of MIR‐378 involved in MDS and clinical interrelation thereof. Methods: Real‐time quantitative methylation‐specific PCR (RQ‐MSP) was performed to evaluate the methylation degree of MIR‐378 5'‐flanking region on bone marrow mononuclear cells collected from 95 de novo MDS patients. Five gene mutations ( IDH1, IDH2, DNMT3A, U2AF1, and SF3B1 ) were detected by high‐resolution melting analysis to further evaluate the clinical relevance of hypomethylation of MIR‐378 . Results: Unmethylated level of MIR‐378 5'‐flanking region was significantly higher in MDS patients than that in controls ( p  = .034). Hypomethylated MIR‐378 was identified in 20 of 95 (21%) cases with MDS. Male patients appeared to be more frequent to harbor MIR‐378 hypomethylation compared to female patients (15/55, 27.3% vs. 4/40, 10.0%, p =  .04). There was no significant difference in age, white blood cell counts, platelet counts, hemoglobin concentration, and karyotypes between the patients with and without MIR‐378 ‐hypomethylation. Distinct distribution of five gene mutations was not observed in the two groups as well. However, MIR‐378 ‐hypomethylated patients had significantly shorter overall survival than those without MIR‐378 hypomethylation ( p =  .036). Moreover, among patients <60 years, hypomethylation of MIR‐378 was confirmed to be an independent adverse prognostic factor by both Kaplan–Meier and Multivariate Cox analyses. Conclusion: Hypomethylation of MIR‐378 5'‐flanking region is an adverse prognosticator in MDS, particularly in patients <60 years. Abstract : Hypomethylation level of MIR‐378 was significantly higher in myelodysplastic syndrome (MDS) patients than that in controls ( p  = .034). MIR‐378 ‐hypomethylated patients had significantly shorter overall survival than those without MIR‐378 hypomethylation ( p  = .036). Both Kaplan–Meier and Multivariate Cox analyses confirmed that hypomethylation of MIR‐378 5'‐flanking region is an adverse prognosticator in MDS, particularly in patients <60 years.